The Effects of Music Therapy on Sleep Quality and its Impact on Occupational Participation Among Geriatrics with Type 2 Diabetes Mellitus - DR.SILPA IMMANUEL VOOLA; MOHAMMED ALI; DR.K.PRINCE; DR.SWAPNA KIRAN (International Journal of Pharma and Bio Sciences, 2018)
Sleep brings restorative and recuperative effects on health. Poor sleep among elderly has been linked to adverse health outcomes particularly (Type 2 Diabetes Mellitus T2DM).This study describes the effects of music therapy on sleep quality and there by its impact on occupational participation which is vital for day to-day living. This was a Quasi experimental pre and post test design study. Geriatric patients, 60 years and above with poor sleep quality [PSQI] score > 5 from two urban nursing homes participated. Each participant in experimental group listened to soft music Participants were asked for preference of music and they were made to listen to the selected music for 45 minutes per night for 2 months. Sleep quality, the main study outcome, was measured by Pittsburg Sleep Quality Index Questionnaire PSQI, Day time functioning using Epworth Sleepiness Scale ESS and occupational participation by Adapted Illness Intrusiveness Rating Scale AIIRS were measured at baseline,1 month and 2 months. Compared to control group, intervention group demonstrated continuous improvement in sleep quality, with a global PSQI score of (t=-0.05, p=0.96) at baseline, (t=3.27, p<0.001) at 1 month, (t=6.80, p<0.001) at 2months. Repeated-measures analysis of variance revealed significant group by time interaction effects in global PSQI scores (p<0.05). Music is a safe and effective alternative mode of intervention with no adverse effects for improving sleep quality of geriatric patients with T2DM admitted in nursing homes. Music can be used as an adjuvant to Occupational therapy.